Randomized control trial of intra-peritoneal instillation of bupivacaine versus placebo for post-operative analgesia after laparoscopic hysterectomy - Dudam, Naval; Barsode, Salil; Borse, Mahindra; Agrawal, Saumya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Laparoscopy is an established method to perform major surgeries, with many advantages over open surgeries. Hysterectomy is a common procedure performed with increased use of laparoscopy, having postoperative pain management is a major issue. Effective pain management promotes early ambulation, lowering the risk of DVT and PE. Methods: The present study aimed to assess effect of bupivacaine intraperitoneally during laparoscopic hysterectomy to reduce postoperative pain. 48 women undergoing laparoscopic hysterectomy under ASA I and II general anesthesia were included, divided into 2 groups, group A receiving 0.25% bupivacaine intraperitoneally; group B receiving saline. A blind observer observed both groups for 6 hours post-surgery or until the VAS was 4, whichever came first, need for rescue analgesia, side-effects, and total dose of analgesia required in 24 hours. Diclofenac sodium and paracetamol was used as rescue analgesia for both groups. Results: There was no significant difference reported in demographic parameters between two study groups. The VAS scores at 6, 12 and 24 hours after laparoscopy was significantly lower in group A than group B. There was significant increase in the time required for 1st analgesia, while amount of analgesia required was significantly low in group A as compared to group B. There were significantly more number of patients in group B who needed opioids than group A. Conclusions: Peritoneal bupivacaine instillation after laparoscopic hysterectomy was found to be useful to reduce the pain as compared to use of saline (placebo), significant reduction in need for analgesics in the postoperative period.